Improving continuity of patient care across sectors: study protocol of the process evaluation of a quasi-experimental multi-centre study regarding an admission and discharge model in Germany (VESPEERA) - Forstner, Johanna; Weis, Aline; Straßner, Cornelia; Uhlmann, Lorenz; Kuemmel, Stephanie; Szecsenyi, Joachim; Wensing, Michel (BMJ open, 2019)
Introduction: Hospital stays are critical events as they often disrupt continuity of care. This process evaluation aims to describe and explore the implementation of the VESPEERA programme (Improving continuity of patient care across sectors: An admission and discharge model in general practices and hospitals, Versorgungskontinuitaet sichern: Patientenorientiertes Einweisungs- und Entlassmanagement in Hausarztpraxen und Krankenhauesern). The evaluation concerns the intervention fidelity, reach in targeted populations, perceived effects, working mechanisms, feasibility, determinants for implementation, including contextual factors, and associations with the outcomes evaluation. The aim of the VESPEERA programme is the development, implementation and evaluation of a structured admission and discharge programme in general practices and hospitals. - Methods and analysis: The process evaluation is linked to the VESPEERA outcomes evaluation, which has a quasi-experimental multi-centre design with four study arms and is conducted in hospitals and general practices in Germany. The VESPEERA programme comprises several components: an assessment before admission, an admission letter, a telephonic discharge conversation between hospital and general practice before discharge, discharge information for patients, structured planning of follow-up care after discharge in the general practice and a telephone monitoring for patients with a risk of rehospitalisation. The process evaluation has a mixed-methods design, incorporating interviews (patients, both care providers who do and do not participate in the VESPEERA programme, total n=75), questionnaires (patients and care providers who participate in the VESPEERA programme, total n=475), implementation plans of hospitals, data documented in general practices, claims-based data and hospital process data. Data analysis is descriptive and explorative. Qualitative data will be transcribed and analysed using framework analysis based on the Consolidated Framework for Implementation Research. Associations between the outcomes of the program and measures in the process evaluation will be explored in regression models. - Ethics and dissemination: Ethics approval has been obtained by the ethics committee of the Medical Faculty Heidelberg prior to the start of the study (S-352/2018). Results will be disseminated through a final report to the funding agency, articles in peer-reviewed journals and conferences. - Trial registration number: http://www.drks.de/DRKS00015183. - Trial status: The study protocol on hand is the protocol V.1.1 from 18 June 2018. Recruitment for interviews started on 3 September 2018 and will approximately be completed by the end of May 2019.